UK Enterprise Policy – A Twist on Real Estate, Austerity And Planning - Lloyd, M.G.; Peel, D. (Journal of Surveying, Construction and Property, 2012)
Times and circumstances change, and sometimes prevailing ideas and thinking do not manage to keep up with those changes. Sometimes an older idea is re-invented and brought back into play – even though context and conditions may have changed. This paper considers such a case - the political reprise of the enterprise zone idea in the UK which was initially designed to address local and regional issues associated with an economic downturn and poorly performing real estate markets in the early 1980s. The enterprise zone model of regeneration was first introduced as a response to the then prevailing depressed economic circumstances and was presented as a way of triggering economic growth and job creation in specific localities or zones. It was introduced as an experiment and the designations lasted until the mid 1990s. In the 2010s economic conditions in the UK are held to be very similar to those prevailing in the early 1980s. There is an evident recession, unemployment, deflated demand, and an over-supply of property. Over and above this, in the UK the policy response is predicated on austerity – with fiscal restraint and public expenditure cutback. Yet there is also a very marked geographical distribution of these circumstances and this has prompted an interest in the earlier enterprise zone idea. Indeed, in 2012 the enterprise zone model is once again being put into place to address the current economic and real estate downturn in the UK.